Aplicación de visión con labview para la detección de frascos con turbiedades - Gordillo Erazo, Lenin Edwin (2009)
The objective of this work is to develop and implement a system for detecting turbidity flasks employing machine vision techniques. The system has been developed using NI Vision library, which provides LabVIEW virtual instruments for machine vision; a USB camera was used as an image capture device. The designed prototype is able to detect impurities in different parts of the bottle, indeed it can detect variations in the tone within the liquid. A turbidity detection system is coupled to the conveyor system and the robotic arm, in order to simulate an industrial environment. The proposed solution employs pattern matching techniques, particle analysis and edge detection